A hátrányos helyzetű és roma fiatalok eljuttatása az érettségihez: Egy különösen nagy hosszú távú költségvetési nyereséget biztosító befektetés - Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, 2006)
– This study estimates the expected long-term budgetary benefits to investing into Roma education in Hungary. By budgetary benefits we mean the direct financial benefits to the national budget. The main idea is that investing extra public money into Roma education would pay off even in fiscal terms. In order to be successful, investments should take place in early childhood. Successful investments are also expensive. But if it is done the right way, such investments more than recoup their costs in terms of extra tax benefits in the future. This study looks at the expected budgetary benefits of a successful investment. It does no deal with how to achieve success. The motivating idea behind our analysis is the notion that investing into somebody's education will lead to benefits not only to the person in question but also to the whole society. We consider these social benefits in a very narrow sense: we make use the fact that in a typical modern society, more education makes people contribute more to the national budget and/or receive less transfers from it. The increased contributions and decreased transfers make up the net budgetary benefits. Net budgetary benefits measure a return on investments into education, very much like returns on any other financial investment. If expected returns more than compensate for such investments, it is in the very narrow interest of the government to invest into Roma education, even setting aside other consideration. We estimate the net benefit of an extra investment (on top of existing pre-school and primary school financing) that enables a young Roma to successfully complete secondary school. We consider an investment that takes place (starts at) at age 4, i.e. we calculate the long-term benefits discounted to age 4. We estimate returns to an investment that makes Roma children complete the maturity examination ('eretttsegi') and opens the road to college, instead of stopping at 8 grades of primary school (or dropping out of secondary school). We consider seven channels: personal income tax on income earned from registered full-time employment, social security contributions paid by employers and employees on earned income, unemployment benefits, means-tested welfare benefits, earning from public employment projects, value added and excise tax on consumption, and incarceration costs. We adjust our estimates by the extra costs of increased secondary and college education. We use large sample surveys, aggregate administrative data, and tax and contribution rules to estimate the necessary parameters. The analysis is nonexperimental and is based on national estimates adjusted for Roma differences. The lack of detailed Roma data and lack of experimental evidence makes interpretation somewhat problematic. We therefore carry out extensive robustness checks for analyzing alternative assumptions. One should keep in mind that, for lack of appropriate data, we leave out important channels such as old-age pensions, disability pensions, childcare benefits, and health care costs. Including most of these channels would most likely increase the estimated benefits to educational investments. Our estimates are therefore most likely lower bounds for the expected budgetary benefits. The results indicate that an investment that makes one young Roma successfully complete secondary school would yield significant direct long-term benefits to the national budget. According to our benchmark estimate, discounted to age 4 (a possible starting age for such an investment), the present value of the future benefits is about HUF 19M (EUR 70,000) relative to the value the government would collect on the representative person in case if she had not continued her studies after the primary school. The benefits are somewhat smaller if (without the suggested early childhood educational investment), the young Roma person finished vocational training school (HUF 15M, EUR 55,000). The estimated returns are sensitive to the discount rate, the assumed wage growth, the college completion rate after secondary school, and the race specific employment and wage differentials (to some extent due to labor market discrimination). But even our most conservative estimates suggest that benefits are least HUF 7M - 9M. We formulate all results in terms of the benefits of an investment that makes one child successfully complete secondary school, for methodological convenience. Naturally, no investment is certain to bring such a result. When comparing benefits to costs, one has to factor in the success probabilities. For example, if an investment increases the chance of secondary school completion by 20 percentage points, i.e. one child out of five gets there as a result of the investment, benchmark benefits relative to 8 grades are HUF 3.8M (19M/5). In other words, 3.8M per child investment would therefore break even with a 20% success rate. Even by looking at our most conservative estimates, any investment with such a success rate is almost sure to yield a positive return if costs are HUF 1.8M or less per child. Overwhelmingly, the benefits would come from increased government revenues, from personal income tax and employer/employee contributions after earned income. Savings on unemployment insurance, welfare benefits and public employment projects are negligible, and savings on incarceration costs are also small. Larger value added tax benefits on consumption are also sizable.
Keywords: J15; I20; I30; 330; Roma Minority; Education; Poverty; Hungary; Roma-Bevölkerung; Bildungsinvestition; Ausbildungsfinanzierung; Öffentliche Einnahmen; Kosten-Nutzen-Analyse; Schätzung; Ungarn